2019
DOI: 10.1097/md.0000000000017171
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of perampanel in adults with mesial temporal epilepsy

Abstract: Mesial temporal lobe epilepsy (MTLE) is a common epilepsy syndrome often refractory to antiepileptic drug (AED) treatment. The purpose of this study was to evaluate the effectiveness and tolerability of perampanel (PER) as add-on treatment for patients of MTLE.We pooled retrospective data from adult patients with MTLE, from a tertiary center in Taiwan, who were prescribed PER between March 2016 and December 2016. The retention, responder, and seizure-free rate as well as the treatment emergent adverse events w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Lin et al 26 reported a 46.9% responder rate at a 6-month follow-up in patients receiving PER therapy for MTLE and hippocampal sclerosis. Among the patients, 11.3% obtained complete seizure-free status during the study period, although half of the patients experienced mild-to-moderate AEs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lin et al 26 reported a 46.9% responder rate at a 6-month follow-up in patients receiving PER therapy for MTLE and hippocampal sclerosis. Among the patients, 11.3% obtained complete seizure-free status during the study period, although half of the patients experienced mild-to-moderate AEs.…”
Section: Resultsmentioning
confidence: 99%
“… 30 32 For drug-resistant patients, studies have also demonstrated the effectiveness of PER in symptomatic epilepsy. 25 26 27 Responder and seizure-free rates have varied widely across studies, with PER being found to offer benefits in about 10%–30% of these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of five studies provided data regarding seizure-free rates. The original seizure-free rates were lower in drug-resistant patients with epilepsy (Rinaldi and De Maria, 2018;Lin et al, 2019) than in those who had PER as their first add-on therapy (Santamarina et al, 2020). The pooled seizure-free rates were 17.0% (95% CI: 0.06-0.29) and 25.0% (95% CI: 0.08-0.42) for the PER plus EIAEDs and PER plus non-EIAEDs groups, respectively (Supplementary Figure S3).…”
Section: Impact Of Enzyme-inducing Aeds On Per Efficacymentioning
confidence: 99%
“…Ikemoto et al, 2019;Kanemura et al, 2019;Lin et al, 2019;Maschio et al, 2019;Stavropoulos et al, 2019;Takahashi et al, 2019;Abril Jaramillo et al, 2020;Coppola et al, 2020;Kim et al, 2020;Liguori et al, 2020;Maschio et al, 2020;Moraes et al, 2020;Pascarella et al, 2020;Santamarina et al, 2020;Toledano Delgado et al, 2020;Yamamoto et al, 2020;Basheikh and Sadler, 2021;Canas et al, 2021;Davis Jones et al, 2021;Im et al, 2021;Inoue et al, 2021;Labate et al, 2021;Lattanzi et al, 2021;Limotai and Jirasakuldej, 2021; Lossius et al, 2021;Nilo et al, 2021;Rodríguez- Osorio et al, 2021;Sagar et al, 2021;Zhang et al, 2021;Chinvarun, 2022;Husni et al, 2022). A diagram summarizing the process of study selection is shown in Figure1.…”
unclassified